Analysis of IMP-1 type metallo-β-lactamase-producing Acinetobacter radioresistens isolated from companion animals. Issue 9 (September 2017) - Kimura, Yui; Miyamoto, Tadashi; Aoki, Kotaro; Ishii, Yoshikazu; Harada, Kazuki; Watarai, Masahisa; Hatoya, Shingo
Abstract: IMP-1 type metallo-β-lactamase-producing (MBL-producing) Acinetobacter radioresistens was isolated from a dog with cystitis and a cat with conjunctivitis. The MBL-producing A. radioresistens isolates were resistant to all of the β-lactam antibiotics used in the sensitivity tests, but were susceptible to gentamicin, amikacin, and minocycline. Also, one of the two strains of A. radioresistens was susceptible to ciprofloxacin and levofloxacin. These two cases were cured by administration of tetracyclines and fluoroquinolones, which elicited a positive result in the sensitivity tests. This report of the isolation of MBL-producing A. radioresistens in companion animals is the first in the world. To prevent the proliferation of MBL-producing bacteria, veterinary hospitals need to be aware of the behavior of MBL-producing organisms.